The Passenger Car Equivalent Factors for Heavy Vehicles on Turbo Roundabouts - Macioszek, Elżbieta (Frontiers in Built Environment, 2019)
The presence of heavy and slower vehicles within the traffic stream significantly reduces traffic capacity. This reduction increases with the higher participation of heavy vehicles in the stream, which, compared to passenger cars, move at a lower speed. Furthermore, they occupy more space on the road, are characterized by a longer reaction time to the road traffic situations, and put greater pressure on the surface structure, etc. In order to conduct analyses related to determination of the conditions in the traffic stream, the traffic stream mixed in terms of composition is converted from real vehicles into passenger car equivalents. For this purpose, the passenger car equivalent factors (Ei) appropriate for a given group of vehicles are used. The paper presents the results of a study aimed to determine the numerical values of passenger car equivalent factors for heavy vehicles (trucks, buses, trucks with trailers, articulated buses) on turbo roundabouts. The research was carried out on turbo roundabouts located in Poland.